Measurements and Observations in the XXI century (MOXXI): innovation and multi-disciplinarity to sense the hydrological cycle. Issue 2 (25th January 2018) - Tauro, Flavia; Selker, John; van de Giesen, Nick; Abrate, Tommaso; Uijlenhoet, Remko; Porfiri, Maurizio; Manfreda, Salvatore; Caylor, Kelly; Moramarco, Tommaso; Benveniste, Jerome; Ciraolo, Giuseppe; Estes, Lyndon; et al.
ABSTRACT: To promote the advancement of novel observation techniques that may lead to new sources of information to help better understand the hydrological cycle, the International Association of Hydrological Sciences (IAHS) established the Measurements and Observations in the XXI century (MOXXI) Working Group in July 2013. The group comprises a growing community of tech-enthusiastic hydrologists that design and develop their own sensing systems, adopt a multi-disciplinary perspective in tackling complex observations, often use low-cost equipment intended for other applications to build innovative sensors, or perform opportunistic measurements. This paper states the objectives of the group and reviews major advances carried out by MOXXI members toward the advancement of hydrological sciences. Challenges and opportunities are outlined to provide strategic guidance for advancement of measurement, and thus discovery.